Effect of Valsalva Maneuver in Measuring Valve Area - Gunes, Hakan; Yucel, Oguzhan; Yilmaz, Mehmet Birhan (Cardiology and Cardiovascular Medicine, 2018)
Background: Echocardiographic measurement of the mitral valve in patients with mitral stenosis is important for treatment and follow-up. The aim of this study was to assess the effect on the valsalva maneuver mitral valve area measurement. Methods: 83 patients with mitral stenosis were included in the study. Valve area of the patients was measured by echocardiography before and after valsalva maneuver. Results: Mitral valve area of the patients were measured as the planimetric being 1.62 ± 0.41, cm2. It was found out that valsalva maneuver had no effect on valve area measured by planimetry. It was observed that valve area measured by PHT decreased with valsalva maneuver while valve area measured by PISA method significantly increased with valsalva maneuver. It was understood from other echocardiographic findings that systolic pulmonary artery pressure, gradients on the cover and velocities decreased with the valsalva. Conclusion: The modes of measurement of mitral valve area are discretely influenced by valsalva maneuver. It is significant to keep in mind potential effects as patients may suffer involuntarily during echocardiography.